DIAGNOSIS OF SOME CARDIOVASCULAR DISEASES USING THE ELECTROCARDIOGRAPH - Khalid Jamal Husham; Zainab Raad Yuosif; Abdullah Ali Mahmoud; Ahmed Zamel Hilal (Journal of Medical Genetics and Clinical Biology, 2024)
Through the patient samples that we obtained from Al-Zahraa Teaching Hospital, some of them were suffering from high rates (a very critical condition), which led to death for some patients, while others were suffering from low rates. Over time, with treatment, their conditions became stable and they were discharged from the hospital. Some Some of them are in critical condition and may take a long time to recover, and this is what was written in the patient records (patient charts) in the hospital. All of these cases and percentages were identified and diagnosed by an electrocardiogram (ECG) device. Cardiovascular diseases were also discussed in detail in In the first chapter, the ECG device is a painless method that helps in diagnosing many common heart problems in the second chapter. In the third chapter, the devices used in measuring (ECG) were discussed, and it was learned how to conduct a medical examination for the patient, the steps of the examination, the reasons for performing the examination, and the uses of the examination. Electrocardiography, the risks of conducting the examination, the type of medical examination for males and females, and its unit of measurement. In the fourth chapter, we discussed the samples obtained from Al-Zahraa Teaching Hospital, explaining each one of them, and comparing them with the healthy sample from a healthy heart